FRI0488 A Phase Iii Pivotal Umbrella Trial of Canakinumab in Patients with Autoinflammatory Periodic Fever Syndromes (Colchicine Resistant FMF, HIDS/MKD and TRAPS). (15th July 2016) - De Benedetti, F.; Anton, J.; Gattorno, M.; Lachmann, H.; Kone-Paut, I.; Ozen, S.; Frenkel, J.; Simon, A.; Zeft, A.; Ben-Chetrit, E.; Hoffman, H.; Joubert, Y.; et al.
Abstract : Background: Periodic fever syndromes (PFS) are a group of rare auto-inflammatory conditions, which includes, among others, cryopyrin-associated periodic syndromes (CAPS), familial Mediterranean fever (FMF), hyper-IgD syndrome/mevalonate kinase deficiency (HIDS/MKD), TNF-receptor associated periodic syndrome (TRAPS). Canakinumab (CAN), a fully human, highly specific anti-IL-1β neutralising monoclonal antibody, is effective in CAPS. 1 IL-1β has been shown to be involved in the pathogenesis of FMF, HIDS/MKD and TRAPS, for whom no approved treatment exists. A series of small open label studies suggested efficacy of CAN in colchicine resistant/intolerant FMF (crFMF), HIDS/MKD and TRAPS. 2, 3 We report the efficacy and safety of CAN from the randomised treatment epoch of a phase III trial in patients (pts) with crFMF, HIDS/MKD or TRAPS. Objectives: Primary objective of this phase III pivotal trial was to demonstrate that CAN 150 mg (or 2 mg/kg for pts ≤40 kg) sc q4w is superior to placebo (PBO) in achieving a clinically meaningful response defined as resolution of the index flare at Day 15 and no new disease flares over 16 wks of treatment. Secondary objectives were: % pts who achieved a physician global assessment of disease activity (PGA) <2 (minimal/none); % pts with C-reactive protein (CRP) ≤10 mg/L; serum amyloid A level (SAA) ≤10 mg/L at Wk 16. Methods: The trial (NCT02059291 ) consists of 3 disease cohorts (crFMF, HIDS/MKD and TRAPS) and 4 study epochs (E1–4): a screening epoch (E1) of up to 12 wks, a randomised treatment epoch (E2) of 16 wks, a randomised withdrawal epoch (E3) of 24 wks and an open-label treatment epoch (E4) of 72 wks. Pts (age ≥2 years) with crFMF, HIDS/MKD or TRAPS with a flare during E1 were randomised (1:1) in E2 to receive CAN or PBO. Safety assessments included adverse events (AEs). Results: Of 181 pts (crFMF, n=63; HIDS/MKD, n=72; TRAPS, n=46) randomised in E2, 6 pts discontinued (5 PBO; 1 CAN). In all 3 disease cohorts, the proportion of pts who were responders for the primary outcome at Wk 16 was significantly higher with CAN vs PBO (Table ). At Wk 16, a significantly higher proportion of pts achieved PGA score <2, CRP ≤10 mg/L and SAA ≤10 mg/L in the CAN group vs PBO in all 3 cohorts (Table ). No new safety findings were reported in the CAN-treated pts through E2 (Table ). Conclusions: These results demonstrated superior efficacy of canakinumab at dose level of 150 mg q4w after a 16 weeks treatment period compared to placebo. The overall safety profile was not distinct from previous controlled studies and expectations in an auto-inflammatory patient population. Disclosure of Interest: F. De Benedetti Grant/research support from: Pfizer, Abbvie, Roche, Novartis, Novimmune, BMS, J. Anton Grant/research support from: Novartis, Pfizer, Abbvie, Roche, SOBI, Consultant for: Novartis, M. Gattorno Grant/research support from: Novartis, SOBI, Consultant for: Novartis, SOBI, Speakers bureau: Novartis, SOBI, H. Lachmann Consultant for: Novartis, SOBI, Takeda, GSK, Speakers bureau: Novartis, SOBI, I. Kone-Paut Grant/research support from: SOBI, Roche, Novartis, Consultant for: Novartis, SOBI, Pfizer, Abbvie, Chugai, S. Ozen Consultant for: Novartis, Speakers bureau: SOBI, J. Frenkel Grant/research support from: Novartis, SOBI, A. Simon Grant/research support from: CSL Behring, Novartis, Xoma/Servier, A. Zeft: None declared, E. Ben-Chetrit Consultant for: Novartis, H. Hoffman Grant/research support from: BMS, Consultant for: Novartis, SOBI, Regeneron, Speakers bureau: Novartis, Y. Joubert Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, A. Speziale Employee of: Novartis, G. Junge Employee of: Novartis